Flexural performance of concrete beams reinforced by gfrp bars and strengthened by cfrp sheets - Falah Hassan, Hassan; Medhlom, Mu'taz Kadhim; Ahmed, Abdullah Sinan; Al-Dahlaki, Mohammed Husein (Case Studies in Construction Materials, 2020)
Glass-fiber-reinforced polymer (GFRP) bars reinforced concrete beams and fortified by carbon-reinforced polymer (CFRP) slips can provide high resilience, high sustainability and reasonable strength for a building scheme. Few experiments contract the combined operation of these products and this was the undertaking's fundamental impetus. The presented study includes an extensive and interesting experimental analysis of the flexural efficiency of reinforced concrete beams GFRP bars and fortified by CFRP sheets. A total of ten GFRP reinforced concrete beams are equipped, experienced and subject to frequent loading series using a four-point bending expedient to complete a catastrophe analysis. The main parameters were GFRP reinforcement ratio and number of CFRP sheets. The central deflection, crack size and concrete strains of the verified beams were verified and contrasted. In this study, the feasibility of using particle image velocimetry (PIV) to detect cracks established in reinforced concrete beams were discovered so that a practical effect can be suggested. The PIV technique has been realistic for analyzing the surface field movement and strain. The test results discovered that the crack sizes and central deflection were considerably decreased by increasing the reinforcement ratio and number of CFRP layers, results characterized that due to its lower cost and strong capacity to observe cracking efficiency, PIV method can be used as a substitute for traditional measuring methods during specific structural tests, exclusively in bending tests.